Correlation of Serum Alanine Aminotransferase with Anthropometric & Biochemical obesity indices in apparently healthy males - Zafar, Uzma; Khalid, Attiqa; Nazir, Sadia; Khaliq, Saba (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The anthropometric obesity indices in this study included; body mass index, waist circumference, waist to hip ratio, mid arm circumference and triceps skin fold thickness. Biochemical obesity indices included; serum high density lipoprotein (HDL), serum triglycerides and serum cholesterol. Aim: To find the correlation of serum alanine aminotransferase (ALT) levels with anthropometric and biochemical obesity indices in apparently healthy male subjects. Methodology: This was an observational descriptive study. Study population included 60 healthy male subjects. They were between 30-50 years of age. All subjects were apparently healthy having no history of diabetes mellitus, hypertension or intake of antihypertensive or lipid/glucose lowering agents. Study data was gathered by a structured questionnaire after written informed consent. Anthropometric measurements, blood pressure and venous blood sample was taken by the standard methods. Data interpretation was carried by SPSS-21. Results: Significant positive correlation of serum ALT was observed with waist circumference (rho=0.371; p=0.008*), mid arm circumference (rho=0.410; p=0.000*), triceps skin fold thickness (rho=0.360; p=0.011*), serum triglycerides (rho=0.493; p=0.005*) and serum HDL (rho=0.423; p=0.000*). Linear regression analysis was applied. Serum ALT was taken as the dependent variable whereas other covariates such as age , serum HDL, triglycerides, cholesterol, body mass index, waist circumference, waist to hip ratio, mid arm circumference and triceps skin triceps skin fold thickness were taken as the predictor variables. Correlation of the mid-arm circumference with serum ALT remained significant after controlling all the given co-variates (p=0.004*). Conclusion: There is significant positive correlation of serum ALT with anthropometric obesity parameters such as waist circumference, mid arm circumference and triceps skin fold thickness. Correlation of anthropometric indices with ALT can provide us with a convenient and an inexpensive tool for prediction of serum ALT levels.